High performance energy saving policy based on IND. (2018) - Liu, Lin; Dai, JingGuo
A novel intelligent network disk (IND) RAM energy management policy is proposed to improve the performance loss of IND caused by old policy. In our method, a replica space is established in the memory of NIC and the copy of high frequency read-only data is put into replica space, thereby reducing the frequency of status changes in IND's memory bank during the I/O process, and extending the duration of low-cost status of IND memory and BUS. Thus, more energy is saved. Meanwhile, replica space can reduce the frequent read-only data transfer via BUS, which can improve the system performance. The experimental results show the new policy can save more than 20% of memory's energy compared to traditional IND energy saving policy and improve the I/O performance of the IND system by more than 10%. Additionally, this strategy can be extended to similar structures with good theoretical and practical value.